Semiotic Thinning of the Surya Majapahit in Java’s Hindu-to-Islamic Transition - Wisnu Adisukma; Ranang Agung Sugihartono; Harmilyanti Sulistyani (FAKULTAS DAKWAH UIN SALATIGA, 2026)
The transformation of visual symbols in contexts of religious transition is a complex phenomenon of cultural communication. This article analyzes the symbolic negotiation of Surya Majapahit, the eight-pointed solar emblem of the Majapahit Empire, as a visual communication medium that persisted across the shift from Hindu-Buddhist to Islamic cosmology in Java. Existing scholarship has largely overlooked how this symbol was actively renegotiated rather than passively inherited. Using a qualitative iconological method integrated with translocality theory, data were collected through artifact observation at temples, tombs, and the Great Mosque of Demak; semi-structured interviews with site custodians and cultural practitioners; and document analysis. The findings reveal a three-phase transformation: (1) full cosmological icon, (2) figurative reduction, and (3) geometric abstraction. The radial core was strategically retained as the communicative core, while Hindu-Buddhist figurative content was gradually eliminated to adapt to the aniconic Islamic visual regime. This symbol, therefore, functioned as a translocal node that actively produced a new Javanese-Islamic locality. The study contributes to intercultural visual communication by proposing “semiotic thinning” as a mechanism of symbolic continuity amid religious change. Limitations and recommendations for heritage interpretation and future research are outlined.